Prevalence of anemia, its associated factors, and impact on quality of life among heart failure with reduced ejection fraction outpatients at the university of Gondar hospital, Ethiopia - Daniel Belay Agonafir; Biruk Mulat Worku; Hailemaryam Alemu; Andinet Azaje Alemu; Gebrehiwot Lema Legese (BMC Cardiovascular Disorders)
Abstract Background Anemia is a frequent comorbidity in patients with heart failure and is associated with increased morbidity, mortality, and reduced quality of life. However, data on anemia prevalence, associated factors, and its prognostic significance are limited in our region. This study aimed to determine the prevalence of anemia in outpatients with heart failure with reduced ejection fraction, identify contributing factors, and evaluate its impact on quality of life at the University of Gondar Comprehensive Specialized Hospital in Northwest Ethiopia. Methods An institution-based cross-sectional study was conducted using an interviewer-administered questionnaire. Data collected included demographic, lifestyle, clinical, biochemical, and echocardiographic characteristics. Health-related quality of life was assessed using the Minnesota Living with Heart Failure Questionnaire. Data were entered into EpiData 4.6 and analyzed using SPSS version 25. Bivariable and multivariable binary logistic regression analyses were performed to identify factors associated with anemia. Variables with a p-value ≤ 0.05 in the multivariable analysis (based on AORs with 95% CIs) were considered statistically significant. Results Among 226 participants (mean age 51.12 ± 13.17 years), the prevalence of anemia in heart failure with reduced ejection fraction patients was 44.2% (95% CI: 37.7–51.0). Anemia was significantly associated with Age ≥ 50 years: AOR 4.18 (95% CI: 1.65–10.58), Hypotension: AOR 3.96 (95% CI: 1.33–11.75), HF duration ≥ 1 year: AOR 4.60 (95% CI: 1.76–11.97), Recent hospitalization: AOR 3.31 (95% CI: 1.42–7.67), Presence of comorbidities: AOR 6.36 (95% CI: 2.28–17.76), Severely reduced ejection fraction: AOR 3.12 (95% CI: 1.29–7.52), and Poor quality of life: AOR 10.52 (95% CI: 3.9–28.36). Conclusion Anemia is highly prevalent among heart failure with reduced ejection fraction patients in this study and is strongly associated with factors indicating advanced disease and comorbidity burden. Importantly, anemia is a significant predictor of poor Health-related quality of life. These findings highlight the need to recognize anemia as a key determinant of morbidity and reduced well-being in HFrEF patients.